ANALISIS KEPUASAN KONSUMEN SHOPEE DIMASA PANDEMIC COVID-19 (Studi Pada Pengguna Shopee di Jakarta Pusat) - Ade Citra Setiawan, " (2021)
The spread of the corona virus or covid-19 is currently increasing, this requires people to carry out various activities at home with the aim of suppressing the spread of the covid-19 virus. with circumstances like this provide a great opportunity for companies providing online buying and selling. Shopee is a company that provides online buying and selling services. Despite this, there are high opportunities for online buying and selling service providers today, problems with the quality of online services and the quality of products provided by shopee. Thus the formulation of the problem made is whether the quality of online services and product quality has an influence on consumer satisfaction. This study aims to prove and analyze the effect of online service quality and product quality on shopee consumer satisfaction. The type of data used in this study is quantitative data with a population of shopee users in Central Jakarta, and a sample of 100 respondents who have or are currently using shopee as a tool for online shopping using purposive sampling method. The analysis technique used is Partial Least Square (PLS) with the help of SmartPLS 3.0 1 Software. The results obtained in this study are (1) the quality of online services has a significant effect on consumer satisfaction, (2) product quality has a significant effect on consumer satisfaction